Analisis Kualitas Pelayanan Pajak Terhadap Kepuasan Wajib Pajak Badan Di Kantor Pelayanan Pajak Madya Malang - Darmawanto, Agus Tri (EP FEB UNS, 2015)
This study aims to determine the perception of corporate taxpayers on the Quality of Service Tax on the Tax Office Madya Malang and to determine the effect of physical evidence, reliability, responsiveness, competence, courtesy, credibility, security, access, communication, and ability to understand customers simultaneously and partially to the satisfaction of corporate taxpayers in KPP Madya Malang. To achieve these goals, used Important Performance Analysis to determine the perception of corporate taxpayers and multiple linear regression analysis is used to determine the effect of service quality on taxpayer satisfaction.Results of the analysis results Important Performance Analysis concluded that the elements of service quality is considered very important by the taxpayer that is physical evidence, competence, access, communication and the ability to understand the customer, the customer has not been implemented as expected, so it was disappointing corporate taxpayers. The elements of the quality of service that courtesy, credibility and security have been successfully implemented KPP Madya Malang and become something that is expected by the taxpayer. The element of quality of service that is the reliability and responsiveness are considered less important for corporate taxpayers and performance of KPP Madya Malang also low.There is a significant effect simultaneously variable physical evidence, reliability, responsiveness, competence, courtesy, credibility, security, access, communication, ability to understand customer satisfaction corporate taxpayers. This means that the level of satisfaction taxpayer depends on the level of service quality, the higher the quality of service, the higher taxpayer satisfaction. Conversely, the lower the quality of service will get low taxpayer satisfaction.Partially, physical evidence, reliability, competence, courtesy, access, communication, and the ability to understand customers is partially a significant impact on taxpayer satisfaction. While Responsiveness, credibility and security does not have a significant influence on taxpayer satisfaction. Keywords : Service Quality, Physical Evidence, Reliability, Responsiveness, Competence, Courtesy, Credibility, Security, Access, Communication, Ability To Understand Customer, Satisfaction Corporate TaxpayersJEL Classification:H20, H21